A New Look at the Living Arrangements of Older Americans Using Multistate Life Tables. (16th October 2018) - Raymo, James M; Pike, Isabel; Liang, Jersey
Abstract: Objectives: We extend existing research on the living arrangements of older Americans by focusing on geographic proximity to children, examining transitions in living arrangements across older ages, and describing differences by both race/ethnicity and educational attainment. Method: We use data from the Health and Retirement Study (HRS) over a period of 10 years (2000–2010) to construct multistate life tables. These analyses allow us to describe the lives of older Americans between ages 65 and 90 in terms of the number of expected years of life in different living arrangements, reflecting both mortality and living arrangement transitions. Results: Americans spend a substantial proportion of later life living near, but not with, adult children. There is a good deal of change in living arrangements at older ages and living arrangement-specific life expectancy differs markedly by race/ethnicity and educational attainment. However, overall life expectancy is not strongly related to living arrangements at age 65. Discussion: Multistate life tables, constructed separately by sex, race/ethnicity, and educational attainment, provide a comprehensive description of sociodemographic differences in living arrangements across older ages in the United States. We discuss the potential implications of these differences for access to support and the exacerbation or mitigation of inequalities at older ages.